2021
DOI: 10.1177/00034894211037413
|View full text |Cite
|
Sign up to set email alerts
|

Parental Views on the Role of Social Media in Pediatric Otolaryngology

Abstract: Objective: Social media is playing an increasingly important role in medicine as a tool for patients and their families to find information and connect with others. The goal of this study is to understand parental views on if and how social media should be incorporated into pediatric otolaryngology by physicians and hospitals. Methods: A survey was distributed to parents of pediatric otolaryngologic patients to assess views on professional social media use by physicians and hospitals. The proportion of parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Many recently published studies have investigated the role of social media in multiple aspects of otolaryngology, from quality of information sources to patient perceptions associated with different conditions. For example, a 2015 study by Saxena et al found cochlear implant patients to have widespread use across different social media platforms, and Ward et al found that parents of pediatric otolaryngology patients had strong interest in using social media as a source for health care information 5,6 . Other articles have analyzed the current online sources of health information for accuracy and relevance such as YouTube videos about laryngeal cancer or otitis media 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recently published studies have investigated the role of social media in multiple aspects of otolaryngology, from quality of information sources to patient perceptions associated with different conditions. For example, a 2015 study by Saxena et al found cochlear implant patients to have widespread use across different social media platforms, and Ward et al found that parents of pediatric otolaryngology patients had strong interest in using social media as a source for health care information 5,6 . Other articles have analyzed the current online sources of health information for accuracy and relevance such as YouTube videos about laryngeal cancer or otitis media 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 2015 study by Saxena et al found cochlear implant patients to have widespread use across different social media platforms, and Ward et al found that parents of pediatric otolaryngology patients had strong interest in using social media as a source for health care information. 5,6 Other articles have analyzed the current online sources of health information for accuracy and relevance such as YouTube videos about laryngeal cancer or otitis media. 7,8 Additionally, studies have investigated social media posts to gauge patient perceptions and experience with certain diagnoses and interventions such as head and neck cancer, pediatric tonsillectomy and tympanostomy tube insertions, and sinus surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that physicians, particularly in the younger age demographic, are familiar with social media, as nearly 90% of physicians aged 26–55 have at least one social media account 16 . However, whereas both physicians and patients have developed social media niches, there may be a disconnect in usages; a recent study demonstrated 67% of parents of pediatric patients undergoing an otolaryngologic procedure wanted their physician to have a social media account related to their practice, whereas only 27% of physicians had social media accounts specifically for health care‐related purposes 2,17 . Beyond this, it has been shown that patients primarily use Twitter and Facebook to interact with other patients, whereas physicians most commonly used LinkedIn and Twitter to contact fellow professionals and for marketing purposes, suggesting somewhat discrete silos in which these groups use their social media accounts 2,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have clearly shown that both clinicians and patients are active on social media for various reasons, often related to their profession or their medical care respectively 1 . Additionally, prior studies demonstrated that there is a desire among certain populations to have their physicians on social media for reasons related to their practice 17 . However, prior to this, there has been no study investigating the relationship of patients' usage of social media with their knowledge and preferences related to its health care implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation